Test of the Randomness of Residuals for the Pseudo-1st Order Kinetic Modelling of Adsorption of the Brominated Flame Retardant 4-bromodiphenyl Ether onto Biochar-immobilized Sphingomonas sp. (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2021)
Test of the Randomness of Residuals for the Pseudo-1st Order Kinetic Modelling of Adsorption of the Brominated Flame Retardant 4-bromodiphenyl Ether onto Biochar-immobilized Sphingomonas sp.
Keywords: Wald–Wolfowitz runs test; Randomness test; pseudo 1st order model; Sphingomonas sp.; adsorption